HYBRID LEARNING: MODEL PEMBELAJARAN TATAP MUKA TERBATAS DI SDIT LUQMAN AL HAKIM SLEMAN - Wildan Nuril Ahmad Fauzi; Yuli Setiawati (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2021)
Hybrid learning is learning that combines face-to-face learning activities with computer and internet technology-based learning. Hybrid learning facilitates students to get materials for learning activities via the internet. This type of research includes qualitative research using descriptive methods. The application of hybrid learning at SDIT Luqman Al Hakim Sleman: First, prepare the curriculum. Second, for every parallel starting from grades one to six, a schedule has been made to carry out face-to-face learning in schools. Third, social standing, such as adjusting the seating distance of students at least 1 meter. Fourth, always wear a mask and or faceshield. Fifth, this learning is only carried out indoors. Sixth, one student with another student should not touch each other. Seventh, the school provides a place to wash hands and soap with running water in every corner of the room and in sufficient quantities. Eighth, all people in the school environment without exception must be in good health. The advantage of this hybrid learning method system is that the interaction process between teachers and students who are present in the teaching and learning process can be applied again. The most significant weakness seen is the problem of providing hybrid learning supporting devices whose prices are still relatively large.